2007
DOI: 10.1118/1.2734726
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of x‐ray spectra emerging from an x‐ray tube. Part II. X‐ray production and filtration in x‐ray targets

Abstract: A new approach to the calculation of the x-ray spectrum emerging from an x-ray tube is proposed. Theoretical results for the bremsstrahlung cross section appearing in the literature are summarized. Four different treatments of electron penetration, based on the work presented in Part I, are then used to generate bremsstrahlung spectra. These spectra are compared to experimental data at 50, 80 and 100 kVp tube potentials. The most sophisticated treatment of electron penetration was required to obtain good agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(165 citation statements)
references
References 33 publications
4
159
0
2
Order By: Relevance
“…In order to predict the imaging performance of different solute choices for the brine, calculate the x-ray spectrum of the incident x-rays [29][30][31] . Include the impact of the core-holder, core assembly and confining fluids on x-ray spectrum.…”
Section: Imaging Strategy Designmentioning
confidence: 99%
“…In order to predict the imaging performance of different solute choices for the brine, calculate the x-ray spectrum of the incident x-rays [29][30][31] . Include the impact of the core-holder, core assembly and confining fluids on x-ray spectrum.…”
Section: Imaging Strategy Designmentioning
confidence: 99%
“…The measurement time of the spectrometer was set to 1000 s. The measured (raw) spectrum was de-convoluted using a Monte Carlo calculated response of the detector. The Penelope2008 Monte Carlo code [20] and the SpekCalc software [22][23][24] were also used to obtain theoretical spectra to be compared with the measured ones. Penelope2008 is a MC code, which reliability and performance have been widely tested [25].…”
Section: Spectral Evaluationmentioning
confidence: 99%
“…In such a system, electrons emitted from the be recognised by the presence of some sort of secondary image in the radio-37 graphs. Although it has often been ignored in spectrum calculations [1], it has 38 been shown that the contribution of the effect cannot be neglected [2].…”
Section: Introductionmentioning
confidence: 99%